Semiology Analysis on Sikerei Tattoo in Taileleu Village, Southwest Siberut, Mentawai Island - Sagugurat, Rosli Penji; Aditiawarman, Mac (Jurnal Ilmiah Langue and Parole, 2019)
This research is entitled "Semiology Analysis on Sikerei Tattoo in Taileleu village, southwest Siberut, Mentawai Island" seen from the perspective of structuralism. This research is limited to a number of basic ideas relating to observations into the following three questions: (1) how the forms of Sikerei tattoo, (2) what the meaning of Sikerei tattoos, and (3) what the function of Sikerei tattoo. The objectives of this research were (1) to explain the forms of Sikerei tattoo, (2) to analyze the meaning of Sikerei tattoo, and (3) to describe the function of Sikerei tattoo. The theory used is from Pierce's about semiotics which is used to answer the purpose of this research. For the method of data analysis, the authors use qualitative research by emphasizing meaning and inner understanding (verstehen), reasoning, definitions of certain situations (in some contexts), more to examine things related to everyday life such as the culture of an area and also semiotic theory. Data collection techniques use literature study techniques in finding data that is relevant to the subject of analysis. This research is qualitative research using the form of field notes, interviews, official personal documents, and photographs or images. The object of this research is Sikerei who is tattooed and the data is tattoos. Finding in this analysis will be focused on the Sikerei tattoo in Taileleu village, southwest Siberut, Mentawai Island. First, the forms of Sikerei tattoo. Second, the meaning of Sikerei tattoo. Third, the function of Sikerei tattoo. Conclusion in this analysis is Sibalubalu as a symbol of health, said health because Sibalubalu is only used by Sikerei where Sikerei is a remedy for sick people in the Mentawai Islands especially in Taileleu village. And suggestion in this thesis is the early achievement that still needs to be developed and continued with more careful study, especially in terms of the research in the field of Sikerei tattoo.